The effect of long term exercise on leptin levels in adolescent wrestlers - Akalin, Tevfik Cem; Gumus, Mustafa; Bayraktaroglu, Taner; Piskin, Ibrahim Etem; Yamaner, Faruk (Progress in Nutrition, 2020)
Study Objectives: The implication of leptin in physical exercise and during its recovery is still unclear. The aim of this study was to examine the effect of eight-month regular well-developed wrestling training in male adolescents on leptin levels, where metabolic and endocrine changes are important. Methods: The sample for this study comprised 69 volunteering male individual subjects who were divided into two different groups. The training program was applied to the 49 male adolescent wrestling group age of 13–15 years (14.4±10.61 years), for 90-120 minutes/day for five days a week during the eight months. The control group consisted of 20 males age between 13–15 years (14.05±0.76 years) who did not receive any planned exercise sessions. Data about the anthropometric and metabolic characteristics including age, body weight, height, body mass index (BMI), waist circumferences, and leptin were obtained. Data were analyzed with the SPSS for Windows 21.0 software. Mann Whitney U Test was used to comparison of independent groups, Wilcoxon Signed Rank Test and Paired Samples t-Test were used to comparison of measurement times, results of analysis were evaluated with 95% confidence interval. Results: There were statistical significantly increase in height, weight, waist circumference, and BMI results of male adolescent wrestlers who did wrestling training for months (p<0.05). No statistical change was found between leptin levels (p>0.05), while leptin levels decreased significantly with puberty (p<0.05). Conclusion: Although some studies indicate that there is a strong relationship between BMI and leptin level, such a relationship was not found in our study. This situation is thought to be caused by physiological changes that are important and effective in adolescence.